Numerical factorization of a matrix-function with exponential factors in an anti-plane problem for a crack with process zone - Livasov, P. (Philos Trans A Math Phys Eng Sci, 2019)
In this paper, we consider an interface mode III crack with a process zone located in front of the fracture tip. The zone is described by imperfect transmission conditions. After application of the Fourier transform, the original problem is reduced to a vectorial Wiener–Hopf equation whose kernel contains oscillatory factors. We perform the factorization numerically using an iterative algorithm and discuss convergence of the method depending on the problem parameters. In the analysis of the solution, special attention is paid to its behaviour near both ends of the process zone. Qualitative analysis was performed to determine admissible values of the process zone's length for which equilibrium cracks exist. This article is part of the theme issue ‘Modelling of dynamic phenomena and localization in structured media (part 1)’.